Les effets du jumelage des infrastructures lourdes de transport sur les territoires : quels enseignements? - Michel Deshaies; Camilo Argibay; Virginie Billon; Jean Carsignol; Emmanuel Chiffre; Luc Chrétien; Axelle De Gasperin; Bertrand Depigny; Angélique Godard; Maxime Huré; Charlotte Le Bris; Harold Mazoyer; et al. (VertigO)
This article reports a research on the effects of pairing of heavy infrastructures such as motorways and high speed lines railways on the functioning and perception of the territory. The ecological impact, effects on the evolution and perception of landscapes as well as governance issues and social acceptability in nearby areas have been specifically studied in three representative of the major types of land pairing observed in France. The comparison of the different elements from the research shows an apparent contradiction on scales of analysis of the appropriateness of the pairing. If it offers an overall benefit for land management with space saving and limiting fragmentation, it also causes a consumption of land with the creation of interstitial spaces, and a strong polarization of space. From the societal perspective, the advantages and disadvantages of the pairing are also related on scales thinking and posture of the actors interviewed vis-à-vis spatial or organizational cuts, or perception of nuisances. Pairing is therefore more a process than a technical solution. Directed downstream, it does not allow for synergies with the territory, but only responds to some isolated subjects like space consumption.